Polysomnographic characteristics and treatment modalities in a referred population of children with trisomy 21 - Gaza, Kaelyn; Gustave, Jodi; Rani, Seema; Strang, Abigail; Chidekel, Aaron (Frontiers in Pediatrics, 2023)
Background Children with Trisomy 21 (T21) are at an increased risk of sleep-disordered breathing (SDB), which can impact daily functioning and cause other health complications. Accordingly, it is imperative to diagnose and treat SDB in this population. Current guidelines recommend screening polysomnogram by age 4 or sooner if clinically indicated. There are limited published studies describing characteristics of SDB in children with T21, particularly in infants and young children. Objective The objective of this study is to characterize SDB and treatment modalities in infants and young children with T21. Methods This is a retrospective review of a cohort of children (≤60 months of age) with T21 who completed a polysomnogram (PSG) between 2015 and 2020 at a pediatric referral center. Demographic information, relevant medical history, polysomnography parameters, and treatment details of these children were collected from EMR. Descriptive and comparative statistics were calculated for the cohort; additional subgroup analysis was completed by age 0–35 months and 36–60 months. Results Most of the cohort met criteria for sleep apnea (84.1%), and airway surgery was the most common treatment modality (71.4%). The mean AHI was high (21.4 events/hour) with a trend towards hypoventilation (mean EtCO2 = 55.9 mmHg; mean percentage of TST with EtCO2 > 50 mmHg 20.8%). Mean arousal index was elevated (32 events/hour). There were no significant differences in SDB by age when we compared children 0–35 months and 36–60 months. Conclusions This cohort of referred children with T21 showed high prevalence of SDB with a trend towards hypoventilation and disrupted sleep quality with no significant differences by age. These data highlight the importance of maintaining a high index of suspicion for SDB in young patients with T21 and obtaining PSG testing to characterize sleep and breathing.